Respon Pertumbuhan dan Hasil Tanaman Kubis (Brassica oleracea L.) terhadap Berbagai Dosis Pupuk Kandang Kotoran Itik dengan Penambahan Abu Sekam pada Tanah Rawa Lebak - Mahdalina Mahdalina; Zarmiyeni Zarmiyeni; Nur Hafizah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
The quality and yield of cabbage can be improved through fertilization, one of which is duck manure as an alternative fertilizer and the addition of husk ash to get optimal results in the lebak wetland. This study aims to determine the doses of dung manure on the growth and yield of cabbage plants. This research was conducted in May-August 2018, located in Teluk Sarikat Village, Banjang District, Hulu Sungai Utara Regency. The study was conducted using a Randomized Block Design (RBD) with a single factor consisting of 5 levels with five treatments. The factors tested were dung manure doses. Observation data were analyzed by variance and DMRT follow-up at 5% level. The results showed that dosing manure with various doses had an affect plant height and several number of leaves but did not affect the weight of the cabbage crop and around the cabbage crop. The best dose of duck manure for the growth of cabbage plants is 10 tons. Ha-1 equivalent to 40 g / polybag (k1).